Feminity & Nature in Moana Movie: An Analysis of Ecofeminism - Komang Artini; Rasiah Rasiah; Ansor Putra (ELITE: Journal of English Language and Literature, 2024)
The study focused on how femininity and nature are portrayed in the Moana movie. The research method used is descriptive qualitative, where data is collected by watching films critically to achieve desired results, taking screenshots and taking notes, and identifying and classifying to support the analysis. Researchers found several aspects of the relationship between femininity and nature in the film Moana after conducting an analysis. Twenty-one data points were identified and classified into three main data groups to support the analysis process carried out by the researcher. One of the important discoveries in this movie is that nature is portrayed as a mother, the same as a woman who will not be angry for no reason. This is reflected in the character of Te Fiti, which also represents motherhood and interconnectedness with nature. Nature is portrayed as a mother, and the film depicts the entire relationship between Moana and nature.